PENGARUH PENGGUNAAAN MODUL HOTS TERHADAP HASIL BELAJAR IPS - Ananda, Rizki; Khairunnisa; Putri, Nurpita; Nania, Resta; Fitriana, Dana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of implementing Higher Order Thinking Skills (HOTS)-based learning modules on elementary school students' learning outcomes in Social Studies. The study employed a qualitative approach using a library research method through a critical review of relevant scientific literature. The research data were obtained from four scientific journals discussing HOTS-based learning, learning module development, and the use of e-modules in elementary education. Data collection was carried out through documentation techniques, including identification, classification, comparison, and analysis of previous research findings. Data were analyzed descriptively through data reduction, data display, interpretation, and conclusion drawing. The findings indicate that the use of HOTS-based learning modules has a positive impact on improving elementary school students' learning outcomes. HOTS-based modules enhance higher-order thinking skills, particularly in analyzing, evaluating, and problem-solving, thereby creating more active, meaningful, and student-centered learning processes. Furthermore, the implementation of HOTS-based modules and e-modules increases students' learning motivation, engagement, and conceptual understanding. Therefore, HOTS-based learning modules can serve as an effective instructional strategy to improve both the learning process and learning outcomes in elementary education.